CONTENT KNOWLEDGE IN GEOMETRY: BASIS ON THE DEVELOPMENT OF INSTRUCTIONAL VISUAL AIDS FOR COLLEGE STUDENTS - Jovelyn P. Gonzales Alyca P. Toraja; Mikko Jan D. Lopez, Edd (Western European Studies, 2023)
The primary purpose of this study was to determine about the content knowledge in Geometry of Bachelor in Secondary Education Major in Mathematics students as basis on the development of instructional visual aids for college students. Data were obtained through a 50- item test questionnaire for the level of content knowledge in geometry and a 15-item checklist for the level of acceptability to determine the level of content knowledge in geometry of BSEd Math students as a basis for the development of instructional visual aids for college students. The data obtained were analysed and assessed using frequency count, percentage, and mean. Results showed that the level of content knowledge of Mathematics major in Geometry was “low‟. In line with this, the most appropriate product to be developed based on the results of the study was instructional visual aids. The instructional visual aid was then evaluated with “very highly acceptable‟ level of acceptability. This led to the conclusion that instructional visual aids substantially met the requirements for a thorough and excellent resource that students and teachers may employ in the teaching-learning process.
Keywords: Content Knowledge; Instructional Visual Aids; Development